Emotional distress among adolescents living with perinatal HIV in India: examining predictors and their mediating and moderating effects - Archana Verma; Krishna Kiran Kota; Sampada Bangar; Girish Rahane; Nayana Yenbhar; Seema Sahay (BMC, 2023)
Abstract Background Development of emotional distress (ED) among adolescents living with perinatally acquired HIV (ALPHIV) affects their adherence behaviour and social and psychological functioning. Data on stressors among ALPHIV demonstrates the gap on the predictors of ED experienced by 'perinatally infected ALHIV' in the Indian socio-cultural milieu. This study aimed to identify the predictors of ED and examine their mediating and moderating role in the development of ED among Indian ALPHIV. Methods Utilizing the sequential exploratory mixed-methods design, 43 qualitative interviews were conducted with ALPHIV, parents/guardians, and health care providers, followed by the cross-sectional survey among 100 ALPHIV (10-19 years). The distress subscale of the Weinberger Adjustment Inventory was used to measure ED. Qualitative data, analyzed using grounded theory were utilized to develop a survey tool. Bivariate and regression analyses were conducted to identify predictors of ED. Mediation and moderation models were tested to examine underlying mechanisms associated with ED. The study was approved by the institutional ethics committee. Results Strong parental control, compulsive asexuality, perceived negatively different from peers, and anger toward parents were the major themes emerging from the qualitative component which eventually led to survey tool domains viz., HIV awareness, parental control, hypervigilance, adolescent-parent relationship, adolescent-parent communication, body image and perceived negatively different from peers (PNDP). Quantitative analysis indicated high ED among ALPHIV and ED was significantly associated with PNDP, anger, body image, and hypervigilance. The relationship between PNDP and ED was significantly mediated by anger, and moderated by body image and hypervigilance. Conclusions The study stresses the need for early mental health interventions for Indian ALPHIV before an ALPHIV develops ED. Focused counseling on anger assessment, body image issues, and self-perception is critical for leading a 'normal' life by ALPHIV. Besides, skill building of primary caregivers is recommended to draw a line between protection and overprotection.